Development of new sources of male sterility in sunflower (Helianthus annuus L.) : Limitations and opportunities: DEVELOPMENT OF SOURCES OF MALE STERILITY IN SUNFLOWER : LIMITATIONS AND OPPORTUNITIES - H P MEENA, (Journal of Oilseeds Research, 2015)
Cytopasmic male sterility (CMS) is a reasonably common characteristic of higher plants. The discovery of a stable source of CMS was the first step towards the practical use of heterosis in sunflower. The second step was the discovery of fertility restoration gene(s). The first CMS (CMS89) in sunflower was reported in descendants of an interspecific hybrid between Helianthus petiolaris Nutt. and cultivated sunflower (the variety Armavirskiy-9345). Although CMS89 or its derivatives are used to produce all commercial sunflower hybrids, more than 72 additional sources ofsunflower CMS have been described by variousscientists. Male sterility may have multiple causes. It can result from adverse growth conditions, from diseases, or from mutations. In this paper, CMS sources obtained by different methods like hybridization (both intraspecific and interspecific crosses), mutagenesis, chemical and spontaneous occurrence of male sterility as well as limitations and opportunities of diverse CMS sources in sunflower were discussed.